THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF DEVELOPING PROFESSIONAL COMPETENCE IN FUTURE BIOLOGY TEACHERS (Web of Teachers: Inderscience Research, 2026)
The modernization of the educational system and the growing demand for high-quality science education require the development of professional competence among future biology teachers. This study examines the theoretical and methodological foundations of professional competence development in pre-service biology teachers within higher pedagogical education. The research is based on competence-based, integrative, personality-oriented, and activity-based approaches. The article analyzes the structure of professional competence, including cognitive, methodological, communicative, digital, and research competencies necessary for biology teachers in contemporary education. Qualitative and theoretical methods such as comparative analysis, synthesis, pedagogical observation, and interpretation of scientific literature were employed. The findings reveal that the effective formation of professional competence depends on interdisciplinary integration, innovative teaching technologies, reflective practice, and continuous pedagogical training. The study highlights the importance of methodological preparedness and practical orientation in teacher education programs. The results contribute to improving pedagogical strategies for preparing competitive and professionally competent biology teachers capable of meeting international educational standards.